Characterization of recombinant Bacillus halodurans CM1 xylanase produced by Pichia pastoris KM71 and its potential application in bleaching process of bagasse pulp - Haniyya Haniyya; Lina Mulyawati; Is Helianti; Phitsanu Pinmanee; Kanokarn Kocharin; Duriya Cantasingh; Thidarat Nimchua (Universitas Gadjah Mada, 2021)
Thermoalkalophilic xylanases promise potential application in pulp biobleaching to reduce the use of toxic chlorinated chemical agents, which are harmful to the environment. In this study, a thermoalkalophilic endoxylanase gene (bhxyn3) originating from Indonesian indigenous Bacillus halodurans CM1 was cloned into yeast expression vector pPICZα A and expressed in Pichia pastoris KM71 under the control of AOX1 promoter. Recombinant P. pastoris expressed the highest final level of xylanase (146 U/mL) on BMGY medium after five days of cultivation. Optimization of xylanase production on a small scale was carried out by varying the methanol concentrations and the optimal xylanase production by the recombinant P. pastoris was observed in the culture with 2% (v/v) methanol after four days of the induction phase. The recombinant xylanase (BHxyn3E) was thermotolerant and alkalophilic, with an optimal temperature at around 55‐65 °C and under pH 8.0. The enzyme activity was slightly induced by K+, Fe2+, and MoO42‐. Enzymatic bleaching of bagasse pulp with no prior pH adjustment (pH 9) using BHxyn3E at 200 U/g oven dried pulp increased the lightness index (L*) and changed substantially the color a index (a*); however, the treatments did not change the whiteness index in a significant way. Therefore, further optimization and assessment such as adjustment of incubation temperature and pH in biobleaching were needed to reduce the use of harmful chemical agents in industrial applications.